2014
DOI: 10.1007/s00299-014-1643-2
|View full text |Cite
|
Sign up to set email alerts
|

2n megagametophyte formed via SDR contributes to tetraploidization in polyembryonic ‘Nadorcott’ tangor crossed by citrus allotetraploids

Abstract: 2 n megagametophyte formation plays an important role in polyploidization in polyembryonic citrus and is valuable for plant improvement. Tetraploid plants are frequently observed in the seedlings of diploid polyembryonic citrus genotypes. However, the mechanisms underlying the formation of tetraploids are still indistinct when apomictic citrus genotypes are used as female parent to cross with tetraploids. Herein, 54 tetraploid progenies, which were unexpectedly obtained previously from four 2x × 4x crosses usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…For example, high temperature can induce 2n female gametes in Populus [39,40]. However, gamete formation is controlled mainly by genes [32,41]. Some genes, such as AtPS1 [42] and JASON [43], were reported to be involved in 2n gamete formation in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, high temperature can induce 2n female gametes in Populus [39,40]. However, gamete formation is controlled mainly by genes [32,41]. Some genes, such as AtPS1 [42] and JASON [43], were reported to be involved in 2n gamete formation in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al [32] reported that SDR was the mechanism of 2n megagametophyte formation in 'Nadorcott' tangor, because the rate of maternal HR varied from 0.00% to 87.80% for 22 SSR markers, with 13 exhibiting a heterozygosity rate <50%. In the present study, the rate of maternal HR of all 25 markers varied from 0% to 100%, with a heterozygosity rate <50% for 10 markers, suggesting that SDR may be the mechanism underlying 2n megagametophyte formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pérez-Tornero et al (2012) obtained triploid hybrids at a frequency of 5.8% to 8.6% in hybridizations between diploid plants of `Verna´ as the female parent and `Fino´ as the male parent. In mandarins, greater differences between genotypes have been observed, ranging from less than 1% for clementines to over 22% for `Sukega´ and `Ortanique´ tangor Aleza et al, 2010b;Wakana et al, 1982;Esen and Soost, 1971;Xie et al, 2014).…”
Section: Parental Origin Of Recovered Plants and Frequencies Of Unredmentioning
confidence: 99%
“…We have observed the same result in eight over the 72 tetraploid recovered plants. Xie et al (2014) also recovered tetraploid plants from the reciprocal hybridization, 2x x 4x, and tetraploid plants were originated as a consequence of 2n female gametes. Here, we have obtained a high number of tetraploid hybrids from 2n pollen gametes (64 over 72 tetraploid recovered plants from only 50 and 32 collected fruits of MCSO and FCSO respectively).…”
Section: Genetic Origin Of Tetraploid Hybrids Recovered From 4x X 2x mentioning
confidence: 99%